Household Behavioral Preferences and the Child Labor-Education Trade-off: Framed Field Experimental Evidence from Ethiopia - Arnab K. Basu; Ralitza Dimova (Institute of Labor Economics (IZA), 2020)
Using data from the Rural Ethiopian Household Survey, which contains a behavioral module, we explore the link between adult risk and time preferences and the incidence and the intensity of child labor. While as expected child labor at both the extensive and the intensive margin is a result of high time discount rates, the narrative behind the positive relationship between adult risk aversion and child labor is more complex. While child labor is clearly the result of risk aversion, more risk averse parents react to their uncertain environments by combining child labor and work as opposed to substituting schooling for child labor.
Keywords: C93; J43; O55; 330; risk and time preferences; education; child labor; Ethiopia